Nutritional and Pharmacological Enhancement of the Gut-Associated Lymphoid Tissue - M Keith Hanna; Kenneth A Kudsk (Canadian Journal of Gastroenterology)
There has been an explosion of research in the field of nutrition over the past quarter century. Clinical studies have demonstrated the effectiveness of providing nutrition by the enteral route in reducing septic morbidity in critically ill patients. These improved outcomes have been substantiated by animal models that show that enteral nutrition decreases gut permeability while maintaining the gut-associated lymphoid tissue (GALT) in mucosal immunity. Evidence points to the important immunological role of the gut in the maintenance of mucosal immunity at both intestinal and extraintestinal sites. The preservation of this mucosal immunity by enteral nutrition is consistent with the lower morbidity seen in severely injured patients who receive nutrition via the gastrointestinal tract. For patients who are unable to be fed by the enteral route and who require parenteral nutrition, several supplements show promise in enhancing the mucosal immune system defenses. The nutritional and pharmacological tactics that may enhance the GALT and thereby maintain mucosal immunity are examined.